Evaluation of the Efficiency of Humic and Agricultural Sulfur on the Growth of Date Palm Tissue offshoots of Barhi cv., irrigated with Saline Water from Shatt Al-Arab River. - Mohsen, Khayun A.; Mohammed, Mariam J.; Alasadi, Ramiz Mahdi Salih (Basrah Journal Of Date Palm Research, 2025)
The aim of this study was to evaluate the combined and individual effects of agricultural sulfur and humic acid on growth and some physiological traits of Barhi date palm offshoots irrigated with saline water of Shatt Al-Arab river. A field experiment was conducted using a factorial design that included ten treatments with different concentrations of humic acid (0, 25, 50, 75, and 100 g palm-1) and sulfur (0 and 200 g palm-1). The results showed that the combined treatment of 100 g humic acid + 200 g sulfur recorded the highest number of leaves (7 leaves) and the highest leaf area (2.28 m²), compared to the control, which recorded the lowest values ​​(3 leaves, 1.29 m²). The contents of chloride and sodium in the leaves decreased to 0.20 and 0.21 mg g-1, respectively, while the leaf calcium (60.1 mg g-1), potassium (4.55 mg g-1), and phosphorus (60.34 mg g-1) increased. Furthermore, the K/Na ratio increased to 22.75. Humic treatments led to increased chlorophyll content (the highest value was 4.214 mg L-1), while proline decreased to 13.98 µg g-1 at the highest humic and sulfur concentrations. The results indicated that, the interaction between sulfur and humic was effective in reducing the salinity stress and improving the physiological traits in date palms.